(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the analgesic effect of perioperative single dose of dexamethasone with control in patients undergoing surgery under general anesthesia. Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the Department of Anaesthesia, Arif Memorial Teaching Hospital associated with Rashid Latif Medical College and Lahore General Hospital, Lahore from July 2019 to December 2019. Materials and Methods: One hundred and forty patients, aged 18-60 years, undergoing surgery under general anesthesia. They were split into two groups, Control (Group C) and Dexamethasone (Group D). The patients in control group were given injection nalbuphine 6-10mg with placebo while those in study group were given injection dexamethasone 0.1mg/kg along with injection nalbuphine 6-10mg. The technique for general anesthesia was standard for both groups. After 12 and 24 hours patients were evaluated for post-operative pain by using visual analogue score (VAS). Results: Mean pain score with dexamethasone was significantly low compared to the placebo group i.e. Dexamethasone: 1.41 vs. Placebo: 2.96, p-value=0.000. Patients were stratified according to age i.e.<40 and >40 years, Sex i.e., male and female patients, BMI i.e., normal, overweight & obese and the mean pain score was notably reduced with Dexamethasone as compared to placebo group across all groups. Conclusion: Dexamethasone at dose of 0.1 mg/kg, is efficacious in minimizing postoperative pain.